Oral History Program Interview: William Rintoul - Rintoul, William
Born in Taft, California in 1922, Rintoul witnessed the 1930s as a teenager. Though he has a fascination with the oil industry, his native perspective provides an alternative to the Dust Bowler account. Rintoul did see the government camps and comments on the plight of the migrants and unemployed locals in Hoover Cities. This interview presents an interesting description of the Grapes of Wrath banning. He includes commentary on the shame people felt working for the WPA and CCC government programs. The term "Okie" can be either a description of origin or derisive to migrants.